2014
DOI: 10.1088/2041-8205/792/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

New Perspective on Galaxy Outflows From the First Detection of Both Intrinsic and Traverse Metal-Line Absorption

Abstract: We present the first observation of a galaxy (z = 0.2) that exhibits metal-line absorption back-illuminated by the galaxy ("down-the-barrel") and transversely by a background quasar at a projected distance of 58 kpc. Both absorption systems, traced by Mg II, are blueshifted relative to the galaxy systemic velocity. The quasar sight-line, which resides almost directly along the projected minor axis of the galaxy, probes Mg I and Mg II absorption obtained from Keck/LRIS and Ly α, Si II and Si III absorption obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 36 publications
5
100
0
Order By: Relevance
“…However, the Mg II absorption harbors a significant component from the ISM at zero velocity. Hence, performing a double-Gaussian fit to the absorption representing the ISM 18 and the wind components (as in Martin et al 2012;Kacprzak et al 2014) shown in Figure 4, we find that the wind speed (at peak optical depth) is about » - V 80 15 out km s −1 . This is the bulk velocity where most of the optical depth is, but the Mg II profile (and the Fe IIprofile) shows absorption up to ∼−150 km s −1 .…”
Section: Windmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the Mg II absorption harbors a significant component from the ISM at zero velocity. Hence, performing a double-Gaussian fit to the absorption representing the ISM 18 and the wind components (as in Martin et al 2012;Kacprzak et al 2014) shown in Figure 4, we find that the wind speed (at peak optical depth) is about » - V 80 15 out km s −1 . This is the bulk velocity where most of the optical depth is, but the Mg II profile (and the Fe IIprofile) shows absorption up to ∼−150 km s −1 .…”
Section: Windmentioning
confidence: 90%
“…As discussed in the next subsection, we can gain insights into the nature of the absorbing gas by comparing the line-ofsight kinematics (with respect to the host galaxy kinematics) to simple models. Such analyses are powerful, but have only been possible in very few cases, such as in Steidel et al (2002), Bouché et al (2012Bouché et al ( , 2013, Kacprzak et al (2010Kacprzak et al ( , 2014,and Schroetter et al (2015) with background quasars and in Rubin et al (2010) and Diamond-Stanic et al (2015) with a bright background galaxy. This analysis requires good constraints on the galaxy systemic redshift and onthe galaxyʼs relative orientation with respect to the quasar sightline.…”
Section: Line-of-sight Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thanks mostly to absorption line spectroscopy, the presence of powerful outflows in galaxies close to the peak of the cosmic star formation (z ≈ 2 − 3), has been firmly assessed (Shapley et al 2003;Steidel et al 2010;Kacprzak et al 2014;Rubin et al 2014;Heckman et al 2015;Schroetter et al 2015). Pushing observations into the Epoch of Reionization (EoR, z > 6) is clearly the next frontier.…”
Section: Introductionmentioning
confidence: 99%
“…One can also undertake a combination of both methods just described above whereby absorption is observed toward a galaxy (down-the-barrel) and toward a QSO transversely projected at some distance (e.g., Kacprzak et al 2014;Bouché et al 2016). I suspect the number of galaxy-QSO pairs will increase dramatically in the future with IFU observations and larger aperture telescope.…”
Section: Gas Accretion Via Pllss and Llss?mentioning
confidence: 99%